Answer:
The graph in the attached figure
Step-by-step explanation:
step 1
Find the equation of the line into point slope form
The equation of the line is equal to
[tex]y-y1=m(x-x1)[/tex]
substitute the given values
[tex]y-1=(2/3)(x+2)[/tex]
step 2
To graph the line find the intercepts
Find the y-intercept
The y-intercept is the value of y when the value of x is equal to zero
so
For x=0
[tex]y-1=(2/3)(0+2)[/tex]
[tex]y=(4/3)+1[/tex]
[tex]y=(7/3)[/tex]
The y-intercept is the point (0,7/3)
Find the x-intercept
The x-intercept is the value of x when the value of y is equal to zero
so
For y=0
[tex]0-1=(2/3)(x+2)[/tex]
[tex]-1=(2/3)x+(4/3)[/tex]
[tex](2/3)x=-(4/3)-1[/tex]
[tex](2/3)x=-(7/3)[/tex]
[tex]2x=-7[/tex]
[tex]x=-7/2[/tex]
The x-intercept is the point (-7/2,0)
step 3
Plot the intercepts to graph the line
see the attached figure